Imaging after treatment in uterine malignancies: Spectrum of normal findings and most common complications. Issue 6 (18th May 2017) - Miccò, Maura; Telesca, Anna Maria; Gui, Benedetta; Grimaldi, Pier Paolo; Cambi, Francesco; Marini, Maria Giulia; Valentini, Anna Lia; Bonomo, Lorenzo
Summary: Uterine malignancies account for the majority of gynaecologic cancers. Different treatment options are available depending on histology, disease grade and stage. Hysterectomy is the most frequent surgical procedure. Chemotherapy and radiation therapy (CRT) represents the preferred therapeutic choice for locally advanced uterine and cervical malignancies. Imaging of the female pelvis following these treatments is particularly challenging due to alteration of the normal anatomy. Radiologists should be familiar with both the expected post‐treatment imaging findings and the imaging features of possible complications to make the correct interpretation and avoid possible pitfalls. The purpose of this review is to show the expected computed tomography (CT) and Magnetic Resonance Imaging (MRI) appearances of the female pelvis following surgery and CRT for uterine and cervical cancer, to illustrate the imaging findings of early and delayed most common complications after surgery and CRT, describing the suitable imaging modalities and protocols for evaluation of patients treated for gynaecologic malignancies.